2012
DOI: 10.1111/all.12003
|View full text |Cite
|
Sign up to set email alerts
|

The single nucleotide polymorphism CRTh2 rs533116 is associated with allergic asthma and increased expression of CRTh2

Abstract: These findings show an association between CRTh2 rs533116 and allergic asthma and suggest this may be mediated by elevated expression of CRTh2, leading to higher numbers of circulating eosinophils and Th2 cytokine production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…We optimized the cycle number to be within the exponential phase of amplification. PCR with 2 µL of DNase/RNase free water (Sigma) instead of cDNA was run as a negative control and cDNA from human Th2 cells (CRTh2 + /CD4 + T cells differentiated in vitro by culturing in Th2-polarizing conditions [44] ) was used as a positive control for DP2. The PCR products were analyzed by 1% agarose gel electrophoresis with ethidium bromide staining and confirmed by sequencing (DNA Core Services Lab, University of Alberta).…”
Section: Methodsmentioning
confidence: 99%
“…We optimized the cycle number to be within the exponential phase of amplification. PCR with 2 µL of DNase/RNase free water (Sigma) instead of cDNA was run as a negative control and cDNA from human Th2 cells (CRTh2 + /CD4 + T cells differentiated in vitro by culturing in Th2-polarizing conditions [44] ) was used as a positive control for DP2. The PCR products were analyzed by 1% agarose gel electrophoresis with ethidium bromide staining and confirmed by sequencing (DNA Core Services Lab, University of Alberta).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies using CRTh2 −/− mice or CRTh2 antagonists showed that this receptor mediates cellular and physiologic responses in models of allergic disease . In humans, CRTh2 + CD3 + T cells are increased in allergic tissues and we and others showed that blood levels of CRTh2 + CD4 + T cells are higher in subjects with allergic airways disease compared with non‐allergic controls . Furthermore, the level of CRTh2 has been reported to be upregulated on eosinophils in eosinophilic esophagitis .…”
Section: Introductionmentioning
confidence: 72%
“…Contrary to expectation, the frequency of A carrier (GA + AA genotypes), which shows lower expression of the CRTH2 gene, was higher in patients with GD (Table 4), and there was no association of this SNP with the intractability of GD. This may be because in patients with GD, who show a higher proportion of Th17 cells [12], the expression level of CRTH2, which induces Th2 cytokine expression [30], and the suppression of Th17 cells by Th2 cells may be too weak to affect the GD intractability [16,18]. In the case of the rs634681 SNP, the frequencies of the T allele and the T allele carrier were higher in patients with mild HD than those with severe HD (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…PGD 2 -CRTH2 signaling induces chemotaxis and expression of Th2 cytokines and is important for allergic inflammation such as asthma [27][28][29]. The single nucleotide polymorphisms (SNPs) in the CRTH2 gene, rs533116, rs545659, rs634681 and rs11571288, have been associated with asthma and allergic sensitization and the functions of these polymorphisms were shown in Table 1 [30][31][32][33][34][35]. Therefore, these CRTH2 SNPs may be associated with chemotaxis of Th2 cells to thyroid gland and induction of Th2 differentiation through IL-4 and IL-13 signaling.…”
mentioning
confidence: 99%